Mezőgazdasági adatok az információforrások tükrében - Csányi, Szilvia; Hegedűsné Baranyai, Nóra (GEORGIKON FOR AGRICULTURE, 2018)
In the most ideal condition we would know everything about the agricultural sector. However, because of the resource capacity limits this is an impossible goal. As follows, we must primarly strive to establish priorities to appropriately collect, store, and evaluate only the relevant data. To compare data of information systems and to draw conclusions from them, we must have complemental, not contradictory, consistent data available. If the methodology is different, in many instances, futher use of data is impossible or rather tiresome. The variable tendencies from year to year can not be handled in research (e.g. Hungarian Agricultural Census- agricultural employment). Futhermore, the lack of transparency can greatly complicate the search for data. Besides, in some cases data are only partially available. Without giving reasons, or even with them, any exact use of information may be complicated for layman users, since in such cases we can rely on estimates at most. Finally, handling or identifying the origin of data is a major challenge. There is some overlap in data usage between the two main institution (Hungarian Central Statistical Office, Research Insitute of Agricultural Economics), that is, vertical and horizontal sharing of data. The derived data substantially complicate the traceability and greatly increase the chance of anomalies and redundant data. Consequently, there are cases when the databases contradict each other and it is almost impossible to determine which piece of data is (more) accurate.
Keywords: agricultural information systems; data; methodology; consistence